User Interface Modeling for Basic English Learning Applications using the Child-Centered Design Method - Kanita Nur Intan Awaliyah; Ati Suci Dian Martha; Veronikha Effendy (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Interactive media convey information through videos or images that can move with computer control in their presentation. Interactive media have a positive effect on children's language development. A language is a tool that humans need to communicate with each other. With the development of technology, especially in communication, Indonesian people have begun to learn English which is used as a means of communication between nations around the world. According to the English Proficiency Index, Indonesia will be ranked 80th out of 112 countries in the world in 2021. This shows that Indonesia is included in the low ability group. One of the efforts to improve English language skills is to introduce basic material from an early age. Children aged 0-6 years quickly absorb and receive various information. This study aims to build a UI modeling of basic English learning applications according to the needs and criteria of kindergarten-age children, which was built using the Child-Centered Design method to analyze the tasks required by the user and evaluate the level of usability using the USE Questionnaire method with a Likert Scale of 1-5. The findings of this study provide user interface design recommendations for basic English learning applications and have a usability score of 88.75. These findings indicate that this application is easy to use and provides a positive experience in learning basic English for kindergarten-age children.